2020
DOI: 10.3390/ani10040674
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Fiber Sources on In-Vitro Fermentation and Microbiota in Monogastrics

Abstract: Feed fiber composition is usually considered as one of the factors that have an impact on digestive tract microbiota composition. The investigations on the level of fermentation and in-vitro digestibility of different fibers are not well understood. The aim of the current study is to determine the effect of different fiber sources on intestinal nutrient digestibility, hindgut fermentation, and microbial community composition under in vitro conditions using pigs’ hindgut as a model. The experimental treatment d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Further work suggested that transitions to the refined diet that lacks soluble fiber is the primary driver of gut microbiota alterations 45 . Therefore, adequate intake of carbohydrates and fiber promotes GI tract health and prevents infections and colonization of the gut by pathogenic microbes 46 . Until now, the exact mechanisms behind the relationship of carbohydrate intake level and gut microbial diversity are still not well studied and should be explored in future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Further work suggested that transitions to the refined diet that lacks soluble fiber is the primary driver of gut microbiota alterations 45 . Therefore, adequate intake of carbohydrates and fiber promotes GI tract health and prevents infections and colonization of the gut by pathogenic microbes 46 . Until now, the exact mechanisms behind the relationship of carbohydrate intake level and gut microbial diversity are still not well studied and should be explored in future investigations.…”
Section: Discussionmentioning
confidence: 99%